Avian malaria in Hawaiian forest birds: infection and population impacts across species and elevations. Issue 6 (30th June 2015) - Samuel, Michael D.; Woodworth, Bethany L.; Atkinson, Carter T.; Hart, Patrick J.; LaPointe, Dennis A.
Abstract : Wildlife diseases can present significant threats to ecological systems and biological diversity, as well as domestic animal and human health. However, determining the dynamics of wildlife diseases and understanding the impact on host populations is a significant challenge. In Hawai'i, there is ample circumstantial evidence that introduced avian malaria ( Plasmodium relictum ) has played an important role in the decline and extinction of many native forest birds. However, few studies have attempted to estimate disease transmission and mortality, survival, and individual species impacts in this distinctive ecosystem. We combined multi‐state capture‐recapture (longitudinal) models with cumulative age‐prevalence (cross‐sectional) models to evaluate these patterns in Apapane, Hawai'i Amakihi, and Iiwi in low‐, mid‐, and high‐elevation forests on the island of Hawai'i based on four longitudinal studies of 3–7 years in length. We found species‐specific patterns of malaria prevalence, transmission, and mortality rates that varied among elevations, likely in response to ecological factors that drive mosquito abundance. Malaria infection was highest at low elevations, moderate at mid elevations, and limited in high‐elevation forests. Infection rates were highest for Iiwi and Apapane, likely contributing to the absence of these species in low‐elevation forests. Adult malaria fatality rates were highest for Iiwi, intermediate for Amakihi at mid and high elevations, and lower for Apapane; low‐elevation Amakihi had the lowest malaria fatality, providing strong evidence of malaria tolerance in this low‐elevation population. Our study indicates that hatch‐year birds may have greater malaria infection and/or fatality rates than adults. Our study also found that mosquitoes prefer feeding on Amakihi rather than Apapane, but Apapane are likely a more important reservoir for malaria transmission to mosquitoes. Our approach, based on host abundance and infection rates, may be an effective alternative to mosquito blood meal analysis for determining vector‐host contacts when mosquito densities are low and collection of blood‐fed mosquitoes is impractical. Our study supports the hypothesis that avian malaria has been a primary factor influencing the elevational distribution and abundance of these three species, and likely limits other native Hawaiian species that are susceptible to malaria.